Improved environmental stability, electrical and EMI shielding properties of vapor‐grown carbon fiber‐filled polyaniline‐based nanocomposite. Issue 5 (25th December 2018) - Kumar, Vipin; Muflikhun, Muhammad Akhsin; Yokozeki, Tomohiro
Abstract : An all polymeric electrically conductive thermoset adhesive resin system is prepared for future lightning strike protection applications. Polyaniline (PANI)‐based hybrid nano‐composite is prepared by incorporating high apparent‐density type vapor grown carbon fiber (VGCF‐H) as additional conductive filler. Electrical, mechanical and electromagnetic interference (EMI) shielding properties of PANI‐dodecylbenzene sulfonic acid (DBSA), and divinylbenzene (DVB) system are improved with addition of VGCF‐H. Different weight percentages of VGCF‐H in the PANI‐DBSA/DVB matrix, are studied, and their effect on composite's properties are investigated. Electrical conductivity up to 1.89 S/cm with the addition of 5 wt% VGCF‐H is achieved, which is almost 300% improvement compared with previous system. However, the maximum flexural modulus is obtained at 3 wt% of VGCF‐H. The change in the electronic structure of PANI with the addition of VGCF‐H is investigated using Fourier transform infrared (FT‐IR) analysis. Rheological study and Differential scanning calorimetry analysis were employed to show the effect of VGCF‐H concentration on curing profile of the nanocomposites. EMI shielding properties of the composite with and without VGCF‐H are measured in X‐band frequencies and compared. Composite with 5 wt% VGCF‐H has shown EMI shielding effectiveness about 51 dB in X‐band, which is higher than the composite without VGCF‐H (around 22 dB). POLYM. ENG. SCI., 59:956–963, 2019. © 2018 Society of Plastics Engineers